Analysis of Popular Learning Theory - Abdul Halim Ade; Neviyarni Neviyarni (Jurnal Neo Konseling, 2021)
Talking about education never ends. The issue of learning is always hot to discuss, both in terms of teachers and students. This article describes the analysis of popular learning theory using relevant literature studies, in the concept that learning theory is an integral part of the teaching and learning process that is used to realize learning for students. In this article, the authors present and analyze four popular learning theories, namely: intelligent character education, quantum learning, accelerated learning, active learning, and hypno teaching.